The Effect of Plyometric Jump to Box Training on Increasing Limb Muscle Power in Badminton Athletes - Ardian Rizki Cahya; Boyke Mulyana; Muhamad Tafaqur; Mulyana Mulyana (Universitas Negeri Semarang, 2024)
The purpose of this study was to determine whether plyometric jump-to-box training can increase leg muscle power in badminton athletes. In this study using an experimental method with a one group pre-test post-test research design. Sampe in this study were UPI Badminton UKM consisting of 12 athletes. The instrument used in this study was vertical jump. Researchers gave treatment in the form of jump to box training for 12 meetings to athletes. Data analysis was carried out using the t-test. The results of data analysis show a significance value of 0.000 <0.05 then Ho is rejected. So it can be concluded that there is a significant effect of Jump to Box Plyometric Exercise on Increasing Limb Muscle Power in Badminton Athletes.